RUSSIAN FAMILY LAW LEGISLATION: REVOLUTION, COUNTER-REVOLUTION, EVOLUTION - NADEZHDA TARUSINA; ELENA ISAEVA (BRICS Law Journal, 2017)
This article analyzes the political and legal aspects of the first decrees of the Soviet government  from 1917 and the codified acts on marriage and family from 1918 and 1926 as large and small  “revolutions” in Russian and Soviet family law. These acts put Russia forward into progressive  positions in comparison with comparable European and American law of that time. The article  analyzes the repressive, “counterrevolutionary” decisions of 1930s and 1940s that pushed family  law, particularly in the sphere of marriage and the legal status of children born out of wedlock,  back to pre-revolutionary imperial standards. It also reviews the normative legal acts on marriage  and the family dating from the “Khrushchev thaw” period. The article identifies the contradictory  and conflicting approaches of legal scholars and legislators to the methodology of legal regulation  of family relations in different periods of political and social history, as well as in our times. The  quality of Russia’s current family legislation, which mainly evolved during the political, economic  and social reforms of the late 20th century, is also assessed. The article traces the influence of  Soviet family law on the content of similar legislation elsewhere in Eastern Europe and the  countries of the former Soviet Union, where there are various levels of legal sovereignty. Their independent legal positions, which are worth comparing with Russia’s family-law doctrine and  legislation, are revealed. The article investigates and evaluates both successful and partially  unsuccessful attempts of modern Russian legislators to adapt the current Family Code and other federal laws regulating family relations to new challenges in the sphere of marriage and family. It speculates on three tendencies of family law doctrine: a certain adherence to the revolutionary ideas of 1917, an orientation toward a return to traditional family values, and a relatively peaceful coexistence with Western doctrines.